2022
DOI: 10.1097/phm.0000000000002039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of high-intensity laser therapy (HILT) on lateral epicondylitis patients: A systematic review and meta-analysis

Abstract: Objectives: Recently, high-intensity laser therapy has been used in the therapeutic protocols for pain management. We aimed to evaluate the clinical efficacy of high-intensity laser therapy versus other different modalities for improving lateral epicondylitis symptoms. Methodology: We conducted a systematic review and meta-analysis on prospective randomized controlled trials from PubMed, Embase, Scopus, Web of Science, and Science Direct until June 2021 using relevant key words. We analyzed the data using Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…HILT stands out for its thermal effects, coverage of larger treatment areas, and energy delivery in a shorter time, thus achieving its therapeutic effects more quickly (following Roscoe Bunsen's Reciprocity law) [13 −15]. Studies regarding the benefits of LILT in myofascial pain and HILT in musculoskeletal pain provide a theoretical basis for considering high-power lasers as a treatment for MFPS [13][14][15]38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HILT stands out for its thermal effects, coverage of larger treatment areas, and energy delivery in a shorter time, thus achieving its therapeutic effects more quickly (following Roscoe Bunsen's Reciprocity law) [13 −15]. Studies regarding the benefits of LILT in myofascial pain and HILT in musculoskeletal pain provide a theoretical basis for considering high-power lasers as a treatment for MFPS [13][14][15]38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HILT is supported for musculoskeletal pain management, including myofascial pain leading to analgesia and increased local circulation. However, few studies have supported its efficacy as a resource in MFPS management [8,[13][14][15]19]. Therefore, the objective of this systematic review with meta-analysis was to evaluate the effectiveness of HILT in a physical therapy program for the treatment of myofascial pain.…”
Section: Effectiveness Of High-intensity Laser Therapy Added To a Phy...mentioning
confidence: 99%
“…Высокоинтенсивная лазерная терапия. УВТ и высокоинтенсивную лазерную терапию (ВИЛТ) сравнивали в нескольких исследованиях по лечению остеоартрита коленного сустава [65][66][67]. Результаты показали, что оба метода приводят к статистически значимому улучшению состояния суставов, однако ВИЛТ оказался более эффективным в снижении боли, улучшении физической функции и снижении инвалидности по сравнению с УВТ.…”
Section: ограничения в доступных методах лечения гонартроза I-ii степениunclassified
“…However, no consensus about the best treatment for improving pain and function in people with LE has been reached; nonetheless, among rehabilitative approaches, therapeutic exercise and physical therapy have reported positive effects on people with LE, regarding pain decrease and tendon strength enhancement [18]. Recently, El Meligie et al [19] concluded that High Power Laser Therapy (HPLT) could improve grip strength, pain, and functional ability at midterm follow-up (5 to 26 weeks). As a matter of fact, with a high-power laser approach, it is possible to reach and stimulate larger and/or deeper areas; consequently, more energy could be transferred into tissues compared to low-level laser therapy (LLLT) [20,21].…”
Section: Introductionmentioning
confidence: 99%